Homozygous WNT9B variants in two families with bilateral renal agenesis/hypoplasia/dysplasia. Issue 10 (19th June 2021) - Lemire, Gabrielle; Zheng, Bixia; Ediae, Grace U.; Zou, Ruobing; Bhola, Priya T.; Chisholm, Caitlin; de Nanassy, Joseph; Lo, Bryan; Wang, Chunyan; Shril, Shirlee; El Desoky, Sherif; Shalaby, Mohammed; et al.
Abstract: WNT9B plays a key role in the development of the mammalian urogenital system. It is essential for the induction of mesonephric and metanephric tubules, the regulation of renal tubule morphogenesis, and the regulation of renal progenitor cell expansion and differentiation. To our knowledge, WNT9B has not been associated with renal defects in humans; however, WNT9B −/− mice have renal agenesis/hypoplasia and reproductive tract abnormalities. We report four individuals from two unrelated consanguineous families with bilateral renal agenesis/hypoplasia/dysplasia and homozygous variants in WNT9B . The proband from Family 1 has bilateral renal cystic dysplasia and chronic kidney disease. He has two deceased siblings who presented with bilateral renal hypoplasia/agenesis. The three affected family members were homozygous for a missense variant in WNT9B (NM_003396.2: c.949G>A/p.(Gly317Arg)). The proband from Family 2 has renal hypoplasia/dysplasia, chronic kidney disease, and is homozygous for a nonsense variant in WNT9B (NM_003396.2: c.11dupC/p.(Pro5Alafs*52)). Two of her siblings died in the neonatal period, one confirmed to be in the context of oligohydramnios. The proband's unaffected brother is also homozygous for the nonsense variant in WNT9B, suggesting nonpenetrance. We propose a novel association of WNT9B and renal anomalies in humans. Further study is needed to delineate the contribution of WNT9B to genitourinary anomalies in humans.